Fundamental motor skills, nutritional status, and environmental associated factors in indigenous children of the villages from Amazonas and Minas Gerais (Research, Society and Development, 2022)
The objective was to investigate the performance in fundamental motor skills, nutritional status, and the environmental associated factors of indigenous children. Sixty indigenous children of the Sateré-Mawé and Pataxós ethnic groups residing in the villages of the state of Amazonas (AM) and Minas Gerais (MG) participated of the study. The results showed greater weight, height, BMI and greater performance in object control skills of indigenous children of MG compared to AM. In MG indigenous, environmental factors afforded more opportunities for physically active practices. Environmental factors associated in a different way with the performance of motor skills of indigenous from AM and MG. We conclude that some factors directed to possible trajectories of greater performance in fundamental motor skills, depend on the interaction between the organism and the experienced environment.